Optical microscopy and proportional reasoning: Constructing scientific-mathematical knowledge through collaborative practices in Elementary Education (Research, Society and Development, 2025)
In contexts of social vulnerability, fostering student interest requires more than curricular changes. It demands participatory and investigative practices. In this scenario, teaching takes on formative and ethical significance by moving away from traditional methods of instruction and embracing collaborative approaches that are grounded in students’ lived experiences. This article aims to present investigative, cooperative and contextualized practices for developing scientific and mathematical skills in primary school students. Developed in a public school in São Paulo (Brazil), the program integrated optical microscopy and applied mathematical problems to promote critical scientific literacy. Based on the Complex Instruction approach and Freirean pedagogy, the study emphasizes the importance of heterogeneous groups, active listening, and appreciating students’ cultural backgrounds as key components of effective teaching. The didactic structure combined scientific observation, problem-solving, and proportional reasoning to promote meaningful, engaged learning. The results demonstrate that interdisciplinary environments strengthen investigative thinking, collective knowledge construction, and educational equity. Furthermore, the study reveals the transformative potential of active methodologies and collaboration in cultivating critical, autonomous, and socially engaged individuals.